Precommissural Fornix in the Human Brain: A Diffusion Tensor Tractography Study - Yeo, Sang Seok (Yonsei University College of Medicine, 2013)
PURPOSE: Other than a single case report, no diffusion tensor tractography (DTT) studies of the precommissural fornix in the human brain have been conducted. In the current study, we attempted to visualize the precommissural fornix in the human brain using DTT. MATERIALS AND METHODS: We recruited 36 healthy volunteers for this study. Diffusion tensor images were scanned using a 1.5-T scanner, and the precommissural fornix was analyzed using Functional Magnetic Resonance Imaging of the Brain (FMRIB) software. Values of fractional anisotropy (FA), mean diffusivity (MD), and tract volume of the precommissural fornix were measured. RESULTS: The precommissural fornix originated from the hippocampal formation on each hemisphere as a crus; both crura were then joined to the body of the fornix. The body of the fornix continued anteriorly to the level just superior to the anterior commissure, where it divided into each column of the precommissural fornix. Each column descended anteriorly to the anterior commissure and terminated in the septal nuclei. Values of FA, MD, and tract volumes of the precommissural fornix did not differ between the right and left hemispheres (p>0.05). CONCLUSION: We believe that the methodology and results of this study would be helpful to future research on the precommissural fornix and in the elucidation of the pathology of diseases involving the precommissural fornix.